PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE JOB ORDER COSTING PADA PT. ABC - Zulkarnain Moeshak Zen; Widodo Widodo (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2016)
There searchaimsto (1) identify the costs to produce the product by PT ABC (2) How is cost accounting applied to PT ABC in producing products (3) Is the read ifference in the accounting treatment of the cost of PT ABC with existing theories. Results from the study showed that the Activities of PT ABC for generating product on sists of the purchase of raw materials, production and sales. Costs incurred in the activities of the company include the cost of raw materials, labor costs and factory overhead costs. Measurements made on purchase of raw materials at first, when the transactions. Recognition ofraw material purchases are recognized when the transaction is recorded in the consolidated purchases of raw materials. Determining the cost of production is based on the amount of use of raw materials in the manufacture of products.The calculation of the cost of production is done manually by adding all the costs in volved to produce the product. Selling on product pricing based on supply and demand of consumer and cost considerations. The calculation in determining the selling price based on estimates done in as impleowner, does not clearly done as acoherent theory of cost accounting.